2021
DOI: 10.1002/ece3.8480
|View full text |Cite
|
Sign up to set email alerts
|

Searching beyond the streetlight: Neonicotinoid exposure alters the neurogenomic state of worker honey bees

Abstract: Neonicotinoid insecticides have been implicated in honey bee declines, with many studies showing that sublethal exposure impacts bee behaviors such as foraging, learning, and memory. Despite the large number of ecotoxicological studies carried out to date, most focus on a handful of worker phenotypes leading to a “streetlight effect” where the a priori choice of phenotypes to measure may influence the results and conclusions arising from the studies. This bias can be overcome with the use of toxicological tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Hence Harwood and Dolezal (2020) suggest that honey bees may be resilient to pesticide stress, and therefore their responses may be context dependent. This leads to the conclusion that effects of insecticides and other pesticides assessed under laboratory conditions may not show their true potential under colony conditions (Tsvetkov & Zayed, 2021). For wild bees, on the other hand, this scenario could be different (Rundlöf et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence Harwood and Dolezal (2020) suggest that honey bees may be resilient to pesticide stress, and therefore their responses may be context dependent. This leads to the conclusion that effects of insecticides and other pesticides assessed under laboratory conditions may not show their true potential under colony conditions (Tsvetkov & Zayed, 2021). For wild bees, on the other hand, this scenario could be different (Rundlöf et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, given that the impact of pesticides depends not only on the fate of the molecule in the body, but also on its interaction with the biological target and consecutive effects on the organism, we could also expect that sulfoxaflor affected nurses and foragers in different manners. A recent study demonstrated that nurse and forager bees were affected in different ways by neonicotinoids at the gene expression level in the brain: while the expression of genes involved in cognition and development was predominantly affected in foragers, the expression of genes involved in metabolism was modified in nurses (Tsvetkov and Zayed 2021). Although, it is not known how such effects might affect honeybee survival or performance, it could help to explain differences in pesticide sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Desnitro-imidacloprid exhibits significantly greater mammalian toxicity than imidacloprid . In addition, neonicotinoids threaten the well-being of bees, aquatic organisms, birds, and mammals. It is known that imidaclothiz can induce oxidative stress and damage to nontarget earthworms . Whether the degradation products of imidaclothiz pose a risk to nontarget organisms is unknown.…”
Section: Introductionmentioning
confidence: 99%